2008
DOI: 10.1007/s00018-008-8047-9
|View full text |Cite
|
Sign up to set email alerts
|

The JNK/AP1/ATF2 pathway is involved in H2O2-induced acetylcholinesterase expression during apoptosis

Abstract: We show that H2O2 increases acetylcholinesterase (AChE) expression via transcriptional activation through c-Jun N-terminal kinase (JNK), since the JNK inhibitor SP600125, but not the extracellular signal-regulated kinase (ERK) pathway inhibitor PD98059 or p38 kinase inhibitor SB203580, attenuated H2O2-induced AChE expression and its promoter activity. Overexpression of hemagglutinin (HA)-JNK increases H2O2-induced AChE expression and its promoter activity, whereas the dominant negative mutant form of JNK suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
1
28
1
1
Order By: Relevance
“…This study tested the hypothesis that contrast media can induce changes in genes that modify histone. Moreover, this study examined the differential effects of different contrast media on expression of activating transcriptional factor 2 (ATF2), a histone-modification gene that is involved in oxidative stress-induced apoptosis via JNK activation [12]. Finally, this study verified that apoptosis occurred in vivo and in vitro study after administration of contrast media.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…This study tested the hypothesis that contrast media can induce changes in genes that modify histone. Moreover, this study examined the differential effects of different contrast media on expression of activating transcriptional factor 2 (ATF2), a histone-modification gene that is involved in oxidative stress-induced apoptosis via JNK activation [12]. Finally, this study verified that apoptosis occurred in vivo and in vitro study after administration of contrast media.…”
Section: Introductionmentioning
confidence: 83%
“…1a). Additionally, several studies have demonstrated that ATF2 has a significant role in the process of apoptosis [12,14]. Thus, subsequent study examined the expression of ATF2 mRNA and ATF2 protein after contrast media treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a transcriptional response should exist to induce the expression of AChE isoforms after apoptotic stimuli. In this sense, AChE promoter contains AP1-like, ATF2 and Smad3/4 binding elements that allow transcriptional expression through c-jun, ATF2 and Smad3 [11,12]. The inhibition of c-jun, or its upstream activating kinase, JNK, abolishes cytotoxic-triggered transcriptional upregulation of AChE [11].…”
mentioning
confidence: 99%
“…In this sense, AChE promoter contains AP1-like, ATF2 and Smad3/4 binding elements that allow transcriptional expression through c-jun, ATF2 and Smad3 [11,12]. The inhibition of c-jun, or its upstream activating kinase, JNK, abolishes cytotoxic-triggered transcriptional upregulation of AChE [11]. Therefore, a fine control of cytotoxic-mediated upregulation of AChE could be also of special interest to manipulate undesirable cellular responses in, for example, Alzheimer's disease.…”
mentioning
confidence: 99%